2010
DOI: 10.1007/s00125-010-1710-3
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measures and glucose levels in a large multi-ethnic cohort of individuals at risk of developing type 2 diabetes

Abstract: Aims/hypotheses We determined: (1) which of BMI, waist circumference, hip circumference and WHR has the strongest association and explanatory power for newly diagnosed type 2 diabetes and glucose status; and (2) the impact of considering two measures simultaneously. We also explored variation in anthropometric associations by sex and ethnicity. Methods We performed cross-sectional analysis of 22,293 men and women who were from five ethnic groups and 21 countries, and at risk of developing type 2 diabetes. Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…Among these, DM2 boasts the largest body of cross-sectional and longitudinal reports, fundamentally directed to the comparison of various anthropometric indices in regards to prediction of this disease [17]. Our findings support the close relationship between obesity and dysglycemic states: Anthropometric measures increased progressively across glycemic states, similar to the results of Koning et al [18] in over 22,000 individuals from the EpiDream study. Comparison of the 3 anthropometric parameters in regards to detection of DM2 revealed WHR and WC to have the greatest predictive capacity in both men and women, surpassing BMI in sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 90%
“…Among these, DM2 boasts the largest body of cross-sectional and longitudinal reports, fundamentally directed to the comparison of various anthropometric indices in regards to prediction of this disease [17]. Our findings support the close relationship between obesity and dysglycemic states: Anthropometric measures increased progressively across glycemic states, similar to the results of Koning et al [18] in over 22,000 individuals from the EpiDream study. Comparison of the 3 anthropometric parameters in regards to detection of DM2 revealed WHR and WC to have the greatest predictive capacity in both men and women, surpassing BMI in sensitivity and specificity.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, Chowdhury et al , 43 in their study of Indian and Swedish men of the same age and BMI, found higher glucose levels in the South Asian men were due to differences in lower leg muscle mass rather than differences in visceral fat, potentially suggesting that physiological differences between ethnic groups may lead to different effects of hip circumference on mortality risk. On the other hand, a powerful confounding effect of hip circumference on the relationship of waist circumference with glucose was observed in the multi-ethnic EpiDREAM study [including Europid (53%), African (6.5%), Latin American (8.1%), South Asian (20.3%) and indigenous (12.1%) participants], which is suggestive of a similar effect in populations other than the South Asian and African populations included here 40 . Further studies including both waist and hip circumference in different population groups and with different outcomes are clearly required 26 …”
Section: Discussionsupporting
confidence: 64%
“…Canoy et al ., 21 in their report on the effects of body fat on risk of coronary heart disease in the European Prospective Investigation of Cancer-Norfolk study, noted that ‘adjustment for hip circumference increased the risk prediction afforded by using waist circumference alone by ≈10% to ≈18% in men and women’ 21 . Likewise, in the large and multi-ethnic Epidemiological arm of the Diabetes Reduction Assessment with Ramipril and Rosiglitazone Medication (DREAM) trial (EpiDREAM) cohort, De Koning et al 40 . observed that the true effect of waist circumference on glucose levels only became apparent after adjustment for both waist and hip circumferences.…”
Section: Discussionmentioning
confidence: 99%
“…Both waist:hip ratio (WHR) and BMI have previously been shown to be strong predictors of type 2 diabetes [21,22]. Systolic and diastolic blood pressure was the average of two measurements in the sitting position using an automatic sphygmomanometer (Spengler SP9).…”
Section: Baseline Data Collectionmentioning
confidence: 99%